STRATEGI PERSONALISASI PRODUK UMKM KULINER TRADISIONAL DI YOGYAKARTA DENGAN METODE RFM DAN K-MEANS CLUSTERING - Liyan, Sur; Yulianto, Dwi Hery; Nugroho, Agung Yuliyanto (Smart Education, 2025)
Abstract: Traditional culinary Micro, Small, and Medium Enterprises (MSMEs) face significant challenges in retaining customers amidst digital competition. This study aims to formulate an effective product personalization strategy for MSMEs by utilizing customer transaction data. We applied the RFM (Recency, Frequency, Monetary) model combined with the K-Means Clustering algorithm to transaction data from 200 culinary MSME customers in Yogyakarta. The analysis results show that customers can be grouped into four homogeneous segments: VIP Customers, Loyal Customers, Potential Customers, and Risky Customers. Based on the unique characteristics of each segment, relevant marketing strategies are formulated, such as exclusive loyalty programs for VIP Customers and reactivation campaigns for Risky Customers. This study contributes by providing a practical, data-driven methodology for MSMEs to improve their retention and marketing effectiveness, filling the existing research gap in the traditional culinary MSME sector. Keyword: RFM (Recency Frequency, Monetary),K-Means Clustering, VIP Abstrak: Usaha Mikro, Kecil, dan Menengah (UMKM) kuliner tradisional menghadapi tantangan besar dalam mempertahankan pelanggan di tengah persaingan digital. Penelitian ini bertujuan untuk merumuskan strategi personalisasi produk yang efektif bagi UMKM dengan memanfaatkan data transaksi pelanggan. Kami menerapkan model RFM (Recency, Frequency, Monetary) yang dikombinasikan dengan algoritma K-Means Clustering pada data transaksi dari 200 pelanggan UMKM kuliner di Yogyakarta. Hasil analisis menunjukkan bahwa pelanggan dapat dikelompokkan menjadi empat segmen homogen: Pelanggan VIP, Pelanggan Setia, Pelanggan Potensial, dan Pelanggan Berisiko. Berdasarkan karakteristik unik setiap segmen, dirumuskan strategi pemasaran yang relevan, seperti program loyalitas eksklusif untuk Pelanggan VIP dan kampanye reaktivasi untuk Pelanggan Berisiko. Penelitian ini berkontribusi dengan menyediakan metodologi praktis berbasis data bagi UMKM untuk meningkatkan retensi dan efektivitas pemasaran mereka, mengisi kesenjangan penelitian yang ada pada sektor UMKM kuliner tradisional.